Charm-quark contribution to KL-->mu+mu- at next-to-next-to-leading order. - Gorbahn, M; Haisch, U (2006)
We calculate the charm-quark contribution to the decay K(L)-->mu(+)mu(-) in next-to-next-to-leading order of QCD. This new contribution reduces the theoretical uncertainty in the relevant parameter P(c) from +/-22% down to +/-7%, corresponding to scale uncertainties of +/-3% and +/-6% in the short-distance part of the branching ratio and the determination of the Wolfenstein parameter rho[over] from K(L)-->mu(+)mu(-) The error in P(c)=0.115+/-0.018 is now in equal shares due to the combined scale uncertainties and the current uncertainty in the charm-quark mass. We find B(K(L)-->mu(+)mu(-)) SD=(0.79+/-0.12)x10(-9), with the present uncertainty in the Cabibbo-Kobayashi-Maskawa element V(td) being the dominant individual source in the quoted error.